Determinants of Hypertensive People Aged 20 to 44 Years Old - Rahayu Chandranita Rini; Honey Ivone Ndoen; Deviarbi Sakke Tira (Journal of Health and Behavioral Science, 2022)
Hypertension is a multifactor disease that can be present in any age group or social-economic group and is due to the interaction of many factors. This study aims to analyze the relationship between family history, consumption of fruits and vegetables, consumption of sodium, consumption of fat, obesity, physical activity, and stress level with the incidence of 20-44 years old hypertension in Oesapa Community Health Center of Kupang City year 2020. This research is a case-control study. The sample consisted of 110 people case samples dan 110 people control samples. Sample selection of the case sample is by simple random sampling and control is by individual matching. The data analysis used was univariate analysis and bivariate analysis with chi-square. The result of the study showed that there is a relationship between family history (p=0,000), fruits and vegetable consumption (p=0,004), fat consumption (p=0,000), obesity (p=0,000), physical activity (p=0,000), and stress level (p=0,000) with the incidence of hypertension aged 20-44 years, while sodium consumption (p=1,000) variable has no relationship with the incidence of hypertension aged 20-44 years.